Chain Message Games as an Effective Intervention for Improving Speech Fluency in Children with Speech Delays - Khoiriyah, Khoiriyah; Purwanta, Edi (Papanda Publisher, 2025)
Speech development serves as a fundamental cornerstone of human development, yet 2.3-19% of preschool children experience speech delays that significantly impact their communication abilities and long-term developmental outcomes. Current educational approaches for addressing speech delays often rely on conventional therapeutic methods that may not adequately engage young learners or accommodate their developmental needs in early childhood settings. This classroom action research employed the Kemmis and McTaggart model to investigate the effectiveness of chain message games in improving speech fluency among five children aged 5-6 years with diagnosed speech delays at TK Masyitoh Sangatta, East Kalimantan. The study was conducted from March to May 2025 through two complete cycles, each comprising two 30-minute sessions. Speech fluency was assessed using a structured observation instrument measuring six dimensions: speech speed, pronunciation clarity, message coherence, social communication response, message completeness, and speaking confidence on a 3-point Likert scale. Substantial improvements were observed across all measured dimensions, with overall speech fluency scores increasing from 13.0% at baseline to 91.3% following the two-cycle intervention. The most pronounced improvements occurred in social communication response and speaking confidence, with all participants achieving high-performance category levels. Progressive improvements were documented throughout both intervention cycles, demonstrating sustained effectiveness of the game-based approach. The findings provide compelling evidence that structured play-based interventions can effectively address speech developmental challenges in early childhood education contexts. The intervention's accessibility and cost-effectiveness make it suitable for widespread implementation in educational settings where traditional speech therapy resources may be limited, offering immediate support for children with speech difficulties while potentially preventing cascading academic and social complications.